PENGEMBANGAN PASAR RAKYAT BERBASIS KEPARIWISATAAN BUDAYA BALI - Dwi Susanti Ida Ayu Made; Anglila Amaral Ni Putu (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
The people's market is one of the places to distribute and market agricultural, food and non-agricultural products. This market is one of the most obvious indicators to see the standard of living of the surrounding communities. The people's market does not only involve economic actors in the agricultural and food sectors but also those in non-agricultural sectors. The agricultural sector development approach that is still being implemented today is agribusiness system. The people's market is part of the agribusiness system, which is included in the subsystem of supporting institutions. This subsystem provides services for upstream agro-industry subsystem, downstream agribusiness subsystem, and marketing subsystem so as to ensure smooth transactions between producers and consumers.